3x-5(x-4)=-6+3x+11

Simple and best practice solution for 3x-5(x-4)=-6+3x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-5(x-4)=-6+3x+11 equation:


Simplifying
3x + -5(x + -4) = -6 + 3x + 11

Reorder the terms:
3x + -5(-4 + x) = -6 + 3x + 11
3x + (-4 * -5 + x * -5) = -6 + 3x + 11
3x + (20 + -5x) = -6 + 3x + 11

Reorder the terms:
20 + 3x + -5x = -6 + 3x + 11

Combine like terms: 3x + -5x = -2x
20 + -2x = -6 + 3x + 11

Reorder the terms:
20 + -2x = -6 + 11 + 3x

Combine like terms: -6 + 11 = 5
20 + -2x = 5 + 3x

Solving
20 + -2x = 5 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
20 + -2x + -3x = 5 + 3x + -3x

Combine like terms: -2x + -3x = -5x
20 + -5x = 5 + 3x + -3x

Combine like terms: 3x + -3x = 0
20 + -5x = 5 + 0
20 + -5x = 5

Add '-20' to each side of the equation.
20 + -20 + -5x = 5 + -20

Combine like terms: 20 + -20 = 0
0 + -5x = 5 + -20
-5x = 5 + -20

Combine like terms: 5 + -20 = -15
-5x = -15

Divide each side by '-5'.
x = 3

Simplifying
x = 3

See similar equations:

| (1+0.00625)^180-1/0.00625 | | 111=-3(1-8m)-5m | | .25(8y+4)-17=-.50(4y-8) | | 5b-9=(-3b)+7 | | -45+22x=0 | | 174=-6+9x | | 7*n=4.5n*n | | 5+(-9)=(-3)+7 | | 4+88-n*n=9n | | P^2+4P+5=0 | | 3x-5(x-4)=6+3x+11 | | 3x+10=3x+20 | | 111=-3(1-8m)5m | | 7/y=20 | | 3+5n=2n*n | | 3(r-6)+2=4(r+2)21 | | 1/2d-5=8 | | (8*2)*(5-n)=n*n-2 | | m/-2=4 | | 4+2n-4=2+4n-2 | | 5/a=4/a-8 | | 3+4n=4+3n | | 8/7*-4 | | 10(x-1)+(x+4)+4x=24 | | 4r-36=2r+14 | | 738.410/9.05 | | 0.5(x-3)-(1.5-x)=5x | | 9+2=10 | | 11x+4=x+195 | | X-5+3=20 | | 11x+4=4x+195 | | 2(5-2y*7)= |

Equations solver categories